High-precision Shack-Hartmann wavefront sensing with a multi-focal diffraction Taiji-lenslet array. (17th November 2021) - Yang, Yaling; Zhang, Yanli; Zhang, Junyong; Li, You; Liu, Dean
Abstract: A Hartmann wavefront sensor is a type of wavefront detection instrument that has been widely used in various fields. Traditional Hartmann wavefront sensors usually comprise a monofocal refraction lenslet array to segment the wavefront at the entrance pupil. Each wavelet is focused at the focal plane along the projection of the lenslet, forming the foci array. Unlike the multifocal self-interference Taiji-lenslet array, a type of multifocal diffraction Taiji-lenslet array was proposed in this study to improve the measurement accuracy using the weighted centroid location algorithm of these multifocal spots, where the latter is more easily designed than the former. An optical experiment was implemented using the multifocal diffraction Taiji-lenslet array to verify its effectiveness. As a type of diffractive lens, a large-aperture Taiji-lenslet array can be easily fabricated via lithography, which has great potential for application in the measurement of large-scale laser beams and optical elements.